Implementation and Comparative Analysis of Test Automation Framework Performance for Functional Testing of Web-Based Applications using the Distance to the Ideal Alternative (DIA) Method - Adiatma, Shidqi; Darmayantie, Astie (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2023)
The importance of functional testing is to ensure the quality of web-based applications so as to improve user experience (user experience) to make it more secure and reliable in ever-increasing market pressure. Can encourage many companies to build high-quality applications and he can release in a short time. Because of this, the testing process must be automated to ensure applications run quickly and effectively. There are several test automation frameworks, specifically for web-based applications that offer effective features and performance to test applications more effectively, such as Katalon Studio, Cypress and WebDriverIO. The purpose of this research is to find the best test automation framework based on performance with certain parameters and sub-parameters. The author runs functional testing on each test automation framework with several test cases and provisions from each framework in a web-based application, and generates reports from each framework with automation testing progress parameters and tool usability parameters using The Distance To The Ideal Alternative method (DIA), and determine the weight for each parameter and sub-parameters. The results of a comparative analysis of test automation frameworks for web-based applications show that WebDriverIO has the best performance compared to other test automation frameworks with a value of 0 in the DIA Method, indicating that WebDriverIO has zero distance from the ideal alternative.